2010
DOI: 10.1103/physrevlett.105.025301
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a High-Temperature Disorder-Induced Mobility in SolidHe4

Abstract: We have carried out torsional oscillator experiments on solid 4He at temperatures between 1.3 K and 1.9 K. We discovered phenomena similar to those observed at temperatures below 0.2 K, which currently are under debate regarding their interpretation in terms of supersolidity. These phenomena include a partial decoupling of the solid helium mass from the oscillator, a change of the dissipation, and a velocity dependence of the decoupled mass. These were all observed both in the bcc and hcp phases of solid 4He. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…Comparing these mass decoupling values to those obtained in our previous experiments 19,20 using single crystals, we see a huge difference. Except for the solid being polycrystalline in the current experiment and a single crystal in our previous work, we used the same cryostat, materials and growth methods in both experiments.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Comparing these mass decoupling values to those obtained in our previous experiments 19,20 using single crystals, we see a huge difference. Except for the solid being polycrystalline in the current experiment and a single crystal in our previous work, we used the same cryostat, materials and growth methods in both experiments.…”
Section: Resultsmentioning
confidence: 76%
“…Crystals of commercially pure 4 He or of 100 ppm 3 He- 4 He mixtures were grown at a constant temperature and pressure. We found that generation of structural disorder within a single crystal caused a large fraction of the mass to decouple from the TO 19,20 . The decoupled mass fraction did not depend strongly on temperature.…”
mentioning
confidence: 98%
“…Furthermore, quantum statistics becomes crucial for describing non-perfect crystals and solid-fluid interfaces at low temperatures. 41,66 Therefore, the final picture for helium solids is certainly far more complex than the one provided by the QHS model in this work.…”
Section: B λ ≈mentioning
confidence: 88%
“…4,33,34 Moreover, bcc also appears under certain conditions as the structure of solid phases composed of light atoms as the helium isotopes. [35][36][37][38][39] In this connection, the bcc lattice of He isotopes is being subject of active research, 38,41 and so is the hcp-bcc equilibrium in 4 He in its own right. [38][39] Furthermore, based on previous experience 9,10,14,15,25 it seems clear that work on the QHS system could give more insights into the study of highly complex real systems.…”
Section: Introductionmentioning
confidence: 99%
“…The exact origin of this broad Q minimum is not clear. In a recent experiment, Eyal and collaborators 18 found a large drop in the period near 1.5 K. We extended the measurements for a few samples in the 6 and 9 cm TOs up to melting points. However, we could not find any period drop larger than the scatter of the data or 0.1 ns at temperatures higher than 0.5 K.…”
mentioning
confidence: 92%